Molecular Characterization of the NLRC4 Expression in Relation to Interleukin-18 Levels. (October 2015) - Zeller, Tanja; Haase, Tina; Müller, Christian; Riess, Helene; Lau, Denise; Zeller, Simon; Krause, Jasmin; Baumert, Jens; Pless, Ole; Dupuis, Josée; Wild, Philipp S.; Eleftheriadis, Medea; et al.
Abstract : Background—: Interleukin-18 (IL-18) is a pleiotropic cytokine centrally involved in the cytokine cascade with complex immunomodulatory functions in innate and acquired immunity. Circulating IL-18 concentrations are associated with type 2 diabetes mellitus, cardiovascular events, and diverse inflammatory and autoimmune disorders. Methods and Results—: To identify causal variants affecting circulating IL-18 concentrations, we applied various omics and molecular biology approaches. By genome-wide association study, we confirmed association of IL-18 levels with a single nucleotide polymorphism in the untranslated exon 2 of the inflammasome component NLRC4 (NLR family, caspase recruitment domain–containing 4) gene on chromosome 2 (rs385076; P =2.4×10 −45 ). Subsequent molecular analyses by gene expression analysis and reporter gene assays indicated an effect of rs385076 on NLRC4 expression and differential isoform usage by modulating binding of the transcription factor PU.1. Conclusions—: Our study provides evidence for the functional causality of single nucleotide polymorphism rs385076 within the NLRC4 gene in relation to IL-18 activation. Abstract : Supplemental Digital Content is available in the text.